2015
DOI: 10.1074/mcp.m114.045468
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Phosphoproteomics Analysis Reveals a Key Role of Insulin Growth Factor 1 Receptor (IGF1R) Tyrosine Kinase in Human Sperm Capacitation*

Abstract: One of the most important changes during sperm capacitation is the enhancement of tyrosine phosphorylation. However, the mechanisms of protein tyrosine phosphorylation during sperm capacitation are not well studied. We used label-free quantitative phosphoproteomics to investigate the overall phosphorylation events during sperm capacitation in humans and identified 231 sites with increased phosphorylation levels. Motif analysis using the NetworKIN algorithm revealed that the activity of tyrosine phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 49 publications
(51 reference statements)
2
52
0
Order By: Relevance
“…According to this, Wang et al in 2015 (14), previously identified 3303 phosphosites belonging to 965 proteins. Comparing our data with the largest description of the sperm phosphoproteome reported so far (14), we found 2692 novel phosphosites being 835 common in both studies. From these 2692 phosphosites, 535 were previously reported in humans in the PhosphoSitePlus database.…”
Section: Discussionsupporting
confidence: 60%
“…According to this, Wang et al in 2015 (14), previously identified 3303 phosphosites belonging to 965 proteins. Comparing our data with the largest description of the sperm phosphoproteome reported so far (14), we found 2692 novel phosphosites being 835 common in both studies. From these 2692 phosphosites, 535 were previously reported in humans in the PhosphoSitePlus database.…”
Section: Discussionsupporting
confidence: 60%
“…This gene belongs to a family of insulin-like growth factors that has important roles in sex determination, testis development, spermatogenesis and steroidogenesis [46]. Interestingly, IGF1R has been implicated in regulating Sertoli cell proliferation and maturation, testis size, and sperm capacitation [47, 48]. Therefore, our findings provide more evidence of the association between IGF1R and male fertility.…”
Section: Discussionmentioning
confidence: 60%
“…We confirmed the presence of KIF9 at the protein level in the spermatocytes using an antipeptide antibody. Proteomic studies have revealed the presence of KIF9 in human sperm [12][13][14] as well as sperm of several mouse species [15]. Thus, based on studies in lower organisms and localization in mammalian sperm, we anticipated that there would be a strong motility defect.…”
Section: Discussionmentioning
confidence: 99%